Tax Compliance of Youtubers in Jakarta Tebet's Primary Tax Service Office - Bhayu Adi Puspita; Arifiani Widjayanti; R. Luki Karunia (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of this study is to determine the causes of tax non-compliance of YouTuber taxpayers, to identify and analyze factors that affect Taxpayer compliance, and determine strategies to improve tax compliance of YouTuber taxpayers at KPP Pratama Jakarta Tebet. In this study, researchers used qualitative descriptive methods. Researchers consider that this method is in accordance with the field to be studied with existing concepts or theories. Based on the results of the study, the compliance of YouTuber Taxpayers at KPP Pratama Jakarta Tebet is influenced by several factors. From a formal point of view, there are weaknesses in online registration and confusion in determining the norm of net income. The lack of cooperation between the Directorate General of Taxes and Google makes oversight difficult. From the material side, the tax that applies to YouTubers is the same as other individual taxes. Economic factors such as compliance costs affect compliance, while financial burdens are not a bottleneck. Behavioral factors showed that educational and moral levels and perceptions of minimal risk affected compliance, while assumptions of unfairness and risk-taking behavior were not constraints. There is a need for further education and optimal socialization in order to improve tax compliance among YouTubers.